A Identidade Cultural na Pós-Modernidade - Teixeira, Elizabeth (Revista Cocar, 2012)
HALL, Stuart. A identidade cultural na pós-modernidade. 10. ed. Rio de Janeiro: DP&A, 2005. The cultural identity in postmodernity HALL, Stuart. Cultural identity in postmodernity. 10. ed. Rio de Janeiro: DP & A, 2005.